2015
DOI: 10.1371/journal.pone.0130010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Work Environment and Musculoskeletal Symptoms among 21-Year-Old Workers: A Population-Based Investigation (2011-2013)

Abstract: BackgroundThe current labour market is becoming more flexible and informal, with job insecurity selectively affecting young workers. However, the role of these increasing adverse psychosocial working conditions on health outcomes remains little known among newly employed workers.ObjectiveTo estimate the associations between psychosocial work environment and musculoskeletal outcomes (widespread pain syndrome features and regional pain) in a population-based sample of young workers.MethodsCross-sectional data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…There are few researches to directly show the association between long working hours and TMD. However, many studies revealed a correlation between long working hours and psychiatric and musculoskeletal problems [ 29 , 30 ]. Meanwhile, biologic (joint trauma), behavioral (psychiatric problems), environmental (head and cervical posture), and cognitive factors (pain threshold) all play a role in the development of TMD symptoms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few researches to directly show the association between long working hours and TMD. However, many studies revealed a correlation between long working hours and psychiatric and musculoskeletal problems [ 29 , 30 ]. Meanwhile, biologic (joint trauma), behavioral (psychiatric problems), environmental (head and cervical posture), and cognitive factors (pain threshold) all play a role in the development of TMD symptoms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contribute to the current literature on job-related well-being among young adults during their transition into work life. The few existing studies on stress among young workers showed that new psychological work environments and unfamiliar working conditions might lead to an elevated perception of chronic stress and musculoskeletal symptoms among job beginners [ 32 ]. Studies among college students indicated that they may become overwhelmed with feelings that there is not enough time to complete all their work adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Subramaniam y Murugesan (2015) [290] India Application of the NMQ in kitchen workers. Lourenco et al (2015) [291] Portugal Application of the NMQ in workers under 21 years of age. Lopes y Pinho (2016) [292] Portugal Application of the NMQ in workers in a recycling plant.…”
Section: Authors Location Observationsmentioning
confidence: 99%
“…Meanwhile, Lourenco et al [291] related the psychosocial risks with MSD in a population of young workers. These researchers concluded that workers at the beginning of their careers are associated with responses of no pain.…”
Section: Varied Occupational Groupsmentioning
confidence: 99%